A halotolerant aldose reductase from Debaryomyces nepalensis: gene isolation, overexpression and biochemical characterization. Issue 33 (7th April 2017) - Paidimuddala, Bhaskar; Krishna Aradhyam, Gopala; N. Gummadi, Sathyanarayana
Abstract : Aldose reductase (AR) catalyzes the conversion of aldoses to polyols, the natural sugar substitutes. Here we provide gene sequence and characteristics of the first-ever halotolerant AR which could be exploited as a potential biocatalyst. Abstract : Aldose reductase (AR) catalyzes the conversion of aldoses to their corresponding polyols in yeasts and filamentous fungi. ARs have the potential to be exploited for the enzymatic production of xylitol, thus the identification and characterization of ARs from novel strains have gained interest. In this study, we chose the novel yeast Debaryomyces nepalensis as a source for an AR gene. For the first time, here we isolated the AR gene from D. nepalensis ( Dn AR) that encodes a protein of 320 amino acids with a predicted molecular weight of 36.7 kDa using the RACE technique. It was heterologously expressed in Escherichia coli as a His-tagged fusion protein and purified. The enzyme showed strict NADPH dependence and broad substrate specificity with high catalytic efficiency for arabinose, xylose and 3-nitro benzaldehyde. Remarkably, it was active and stable in the presence of high concentrations of salts (KCl/NaCl), thus exhibiting halotolerance. It showed 75% and 45% activity at 0.5 and 1 M concentration of salts respectively. Enzyme half-lifetime at 1 M KCl and 1 M NaCl was found to be 30 h and 16.5 h respectively. Furthermore, to explore the structural basis of its halotolerance, we built a homology model of Dn AR. Surprisingly, we found that the existence of a uniform negative electrostatic potential over the protein surface, which is one of the known mechanisms governing protein halotolerance. Therefore, Dn AR could be exploited as a biocatalyst to develop an enzyme based bioprocess for xylitol production from lignocelluloses. Moreover, this is the first report providing the genetic sequence and biochemical characteristics of a halotolerant aldose reductase.